Studi Minat Siswa dalam Mengikuti Senam PAUD Ceria di TK Bina Ana Prasa Kecamatan Benowo Surabaya - Mira Pradipta Ariyanti Pradipta Ariyanti Ariyanti (PG-PAUD Trunojoyo, 2018)
The formulation of the problem in this research is how is the interest of students in following gymnastics early childhood at TK Bina Ana Prasa Benowo Surabaya? This study aims to find out what causes student interest in following gymnastics PAUD Ceria in kindergarten Bina Ana Prasa Benowo Subdistrict Surabaya. In this research The method used is the method of observation with the type of Descriptive research. The population in this study were all students who participated in PAUD Ceria gymnastics activity which amounted to 70 people and the samples used in this study were as many as 30 people conducted in total sampling that included all individuals or members of the population into a sample. There are some problems that researchers found that affect the interest of Bina Ana Prasa kindergarten students in following the Eccentric gymnastics and the problem is categorized as follows, namely the influence of self-desire to do gymnastics PAUD Ceria with 50% percentage, encouragement and support from sports teachers with 55 percentage %, and the desire to do gymnastics PAUD Cheers for a friend with a percentage of 20%, as well as eager to follow PAUD Ceria gymnastics out of school with a percentage of 60%.